2022
DOI: 10.1002/jcc.27039
|View full text |Cite
|
Sign up to set email alerts
|

Pressure‐assisted decomposition of tricresyl phosphate on amorphous FeO using hybrid quantum‐classical simulations

Abstract: The moving components of combustion engines are operated under harsh conditions of high pressures and temperatures. Extreme‐pressure anti‐wear additives, such as tricresyl phosphate (TCP), are mixed with base oil to prevent wear through the formation of a lubricant film on the substrate. We studied the effect of liquid pressure on the decomposition pathway of TCP in base oil molecules (2,5‐dimethylhexane) using hybrid quantum‐classical simulations with density functional theory for electrons. At a temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
2
1
0
Order By: Relevance
“…As shown in Figures and S1, TCP molecules exhibit a significantly higher number of P–O Lub bond cleavages but a limited number of C–O Lub bond cleavages on all three substrates. The barrier energies of C–O Lub and P–O Lub bond cleavages on amorphous FeO substrate at a pressure of 0 GPa are about 3.0 and 2.2 eV, respectively . This indicates that TCP molecules primarily experience P–O bond cleavages on iron-based substrates, consistent with findings in the experiments. , In contrast, the dissociation behavior of TNBP molecules is dependent on the substrate material.…”
Section: Results and Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…As shown in Figures and S1, TCP molecules exhibit a significantly higher number of P–O Lub bond cleavages but a limited number of C–O Lub bond cleavages on all three substrates. The barrier energies of C–O Lub and P–O Lub bond cleavages on amorphous FeO substrate at a pressure of 0 GPa are about 3.0 and 2.2 eV, respectively . This indicates that TCP molecules primarily experience P–O bond cleavages on iron-based substrates, consistent with findings in the experiments. , In contrast, the dissociation behavior of TNBP molecules is dependent on the substrate material.…”
Section: Results and Discussionsupporting
confidence: 83%
“…The formation and cleavage of chemical bonds were determined by the bond order with a cutoff value of 0. 45 This indicates that TCP molecules primarily experience P−O bond cleavages on iron-based substrates, consistent with findings in the experiments. 22,23 In contrast, the dissociation behavior of TNBP molecules is dependent on the substrate material.…”
Section: ■ Simulation Methodssupporting
confidence: 84%
“…58 Due to the significant additional computational expense of simulating non-reactive base oil molecules, these were excluded from the majority of our simulations. Although some reactive NEMD simulation studies of lubricant additive mechanochemistry have simulated the base oil molecules, 59,60 the vast majority have not. 21,46,[61][62][63] Previous NEMD simulations of sulfur-based additives with ReaxFF have shown that there were only minor differences when unreactive base oils were included in the simulations.…”
Section: System Setupmentioning
confidence: 99%